Biomechanical analysis of accessory tendon graft augmentation for primary gastrocnemius tendon reconstruction in dogs. Issue 5 (3rd May 2021) - Duffy, Daniel J.; Chang, Yi‐Jen; Fisher, Matthew B.; Moore, George E.
Abstract: Objective: To evaluate the effect of accessory tendon graft (ATG) augmentation as an adjunct to a core locking‐loop (LL) and epitendinous suture (ES) repair in a gastrocnemius tendon (GT) model. Study Design: Randomized, ex vivo, biomechanical. Population: Twenty‐two canine GT musculotendinous constructs. Methods: GT repair constructs were randomly divided into two groups ( n = 10/group). After transection, paired GT were repaired with LL + ES alone or with concurrent ATG augmentation. Yield, peak and failure loads, tensile loads required to create 1 and 3 mm gapping, and failure modes were evaluated. Four GT were used as intact controls for validation of testing methodology. ATG constructs were compared to LL + ES and control specimens. Results: Yield ( p < .0001), peak ( p = .0001) and failure loads ( p = .0003) were greater when ATG was used for repair. Greater force was required to cause 1 mm ( p = .0001) and 3 mm ( p = .0002) gap formation in the ATG group, however, the frequency of gap formation did not differ between groups. All repaired constructs failed exclusively by suture pull‐through. Conclusion: Autologous ATG augmentation as an adjunct to primary GT repair increased yield, peak and failure forces by approximately 1.6×, 1.9×, 1.8× respectively and required 2.1× greater force to cause 1 and 3 mm formation respectively compared to LL + ES repairs alone. Clinical Significance: ATG augmentation should be considered as an autologous method to support and strengthen the primary GT repair. These results justify studies to determine the effect of ATG on clinical function following graft harvest in dogs.